Analysis of the impact of different nanoparticle metal oxides as fuel additives in compression ignition engine performance. (December 2020) - Abdallah, A.M.; Abdel-Rahman, A.A.; Elwardany, A.E.
Abstract: Biodiesel is used as an alternative fuel in combustion engines. It produces lower carbon monoxide, unburned hydrocarbon, and particulate emissions when compared to that neat diesel. This experimental work aims to upgrade the characteristics of gases emitted, performance and combustion of CI engine. The engine model is a HATZ-1B30-2 Gunt, single cylinder, four stroke, direct injection, air cool CI engine. Experiments are done at 2000 rpm constant speed and dissimilar loads using fuel blends. Three different nanoparticles of metal oxides are used as an additive in different blends of fuel with a dose of 50 ppm. Visual solubility tests are performed for the fuels. The newly developed fuel is burned immediately after preparation to avoid phase separation. The B30–50 MgO nanoparticles showed a 19% reduction in BSFC compared to diesel fuel. CO emission is decreased by 28 % when using D100–50 Al2 O3 and NO x emission is decreased by 7 % when using B30–MgO. For the blends containing nanoparticle additives, there is an increase in break power (BP), heat release rate (HRR), and cylinder pressure. Also, there is a reduction in break specific fuel consumption (BSFC), and emissions such as nitrogen oxides (NO x ) and carbon monoxide (CO) as in comparison with the neat diesel fuel.